Princip a význam metody arrayCGH v hemato-onkologii - Jarosová, M; Pospísilová, H; Plachý, R; Divoká, M; Holzerová, M; Papajík, T; Koptíková, J; Indrák, K (Casopis lekaru ceskych, 2006)
Identification of chromosomal changes and variation in DNA copy number allows us to understand pathogenesis of tumors. To the frequently diagnosed chromosomal changes belong acquired gains and losses of chromosomal regions carring genes involved in cellular proliferation and differentiation as well as oncogenes and tumor suppressor genes. The determination of gene changes is limited by techniques used for their identification. The introduction of genom-wide microarray technology, resolution has rapidly increased. Array comparative genomic hybridization (arrayCGH) offers higher resolution for genome-wide detection of chromosomal alteration and it is able to analyze hundreds to thousands of genes presented on microarray in one experiment. The aim of this study was to perform arrayCGH technology and to stress its value for the identification of chromosomal imbalances in hematological malignancies.
Keywords: Nucleic Acid Hybridization; Oligonucleotide Array Sequence Analysis; lidé; hybridizace nukleových kyselin; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; hematologické nádory; Hematologic Neoplasms; Humans